Mapping and validation of a novel major QTL for resistance to stripe rust in four wheat populations derived from landrace Qishanmai - Jiang, Xu; Wang, Zhen; Feng, Jing; Du, Ziyi; Zhang, Zhongjun; Zhang, Yibin; Che, Mingzhe; Ren, Junda; Wang, Haiguang; Quan, Wei (Frontiers in Plant Science, 2023)
Wheat yield has been constrained by stripe rust disease globally. A wheat landrace (Qishanmai, QSM) consistently showed lower stripe rust severities in multiple year studies than susceptible check varieties including Suwon11 (SW) at the adult plant stage. To detect QTL for reducing the severity in QSM, 1218 recombinant inbred lines (RILs) were developed from SW × QSM. QTL detection was conducted firstly using 112 RILs selected for similarity in pheno-morphological characters. The 112 RILs were assessed for stripe rust severity at the 2nd leaf, 6th leaf and flag leaf stages under field and greenhouse conditions, and genotyping was done primarily with a single nucleotide polymorphism (SNP) array. On the basis of these phenotypic and genotypic data, a major QTL (QYr.cau-1DL) was detected on chromosome 1D at the 6th leaf and flag leaf stages. Further mapping was conducted by genotyping 1218 RILs using new simple sequence repeat (SSR) markers, which were developed by referring to the sequences of the wheat line Chinese Spring (IWGSC RefSeq v1.0). QYr.cau-1DL was mapped within a 0.5 cM (5.2 Mb) interval delimited by the SSR markers 1D-320.58 and 1D-325.79. These markers were applied to select for QYr.cau-1DL by screening F2 or BC4F2 plants of the wheat crosses RL6058 × QSM, Lantian10 × QSM and Yannong21 × QSM. F2:3 or BC4F2:3 families derived from the selected plants were assessed for stripe rust resistance in the fields of two locations and in a greenhouse. Wheat plants carrying the resistant marker haplotype in homozygous state for QYr.cau-1DL showed lower stripe rust severities (by 44% to 48%) than plants lacking this QTL. The trial of RL6058 (a carrier of Yr18) × QSM also indicated that QYr.cau-1DL had larger effect than Yr18 on reducing severity; they acted synergistically, yielding an elevated level of stripe rust resistance.